TEMPERATURE DEPENDENCE OF THE MAGNETIC ROTATION PROCESS OF KAOLINITE MICROCRYSTALS CONTAINING PARAMAGNETIC IMPURITY IONS DISPERSED IN LIQUID MEDIUM - Uyeda C.; Sakakibara M.; Tanaka K. (My University, 2003)
Temperature dependencies of magnetic rotation were measured in micron-sized silicates dispersed in ethanol for two different samples of kaolinite. Magnetic rotation proceeded by balance between thermal agitation energy and magnetic anisotropy energy. Measurements were performed between 195 and 343 K. The field intensity required to achieve magnetic alignment of microcrystals increases with temperature, because of the temperature dependence of paramagnetic anisotropy, and the temperature dependence of thermal agitation energy. The results indicate that the values of magnetic anisotropy of nonmagnetic materials might partially derive from the paramagnetic moments, which derive from paramagnetic impurity ions. The present experiment provides a technical basis for determining the precise values of diamagnetic anisotropy (Δχ)DIA from minerals which have a concentration of paramagnetic ions and do not form a single crystal large enough to allow bulk Δχ measurements. The values of (Δχ)DIA can be obtained by extrapolating the Δχ-T relations, which follow the Curie law, to the temperature limits.
Keywords: MAGNETIC ALIGNMENT; DIAMAGNETIC ANISOTROPY; KAOLINITE; SHEET-SILICATE; PARAMAGNETIC ANISOTROPY; MICRON-SIZED CRYSTAL; CERAMIC MATERIAL